Sądzenie tych którzy nie mogą być sądzeni – procesy kolaborantów w Izraelu - Tall, Boaz (Zagłada Żydów. Studia i Materiały, 2006)
As part of the purification and self-cleansing atmosphere in the newly liberated countries of Europe following the end of World War II, dozens of Jews were put on trial for their actions during the war, and some were even convicted. This dispensation of justice did not pass by the young Jewish state. In 1950, the "Nazis and Nazi Collaborators (Punishment) Law, 5710-1950" was passed in Israel. Although the law was supposedly intended to bring to justice Nazis, in fact the majority of defendants were Jews. Until the beginning of the 1960s, close to 40 Jewish survivors of the holocaust who were accused of collaboration with the Nazis, were put on trial under this law. Most of them had been prisoners with special duties in Nazi camps, which were known by the collective name, "Kapo".